L'Hiver de l'Amour Bis. - Ballard; Blair, Dike; Bonami, Francesca; Brautigan, Richard; Deitcher, David; Delhomme, Sophie-Anne; Foucault, Michel; Gombrowicz, Witold; Guattari, Félix; Hoover, Chris; Hustvedt, Siri; Joisten, Bernard; et al. (Paris : ARC Musée d'Art Moderne de la Ville de Paris, 1994)
Aballéa, Martine ; Ariyoshi, Shuji ; Benning, Sadie ; Boudier, Véronique ; Clark, Larry ; Collishaw, Mat ; Edelkoort, Li ; Edström, Anders ; Garmon, Ami ; General Idea ; Grenet, Yves ; Guilleminot, Marie-Ange ; Hajamadi, Fariba ; Hammons, David ; Hansen, Markus ; Hempel, Lothar ; Höller, Carsten ; Lambert, Alix ; van Lamsweerde, Inez ; Lévêque, Claude ; Margiela, Martin ; Marisaldi, Eva ; van Oost, Jan ; Pigato, Valerie ; Piper, Adrian ; Robbins, David ; Santos, René ; Scher, Julia ; Tillmans, Wolfgang ; Tiravanija, Rirkrit ; Viktor & Rolf ; Vilmouth, Jean-Luc ; Zittel, Andrea
biografie
L'Hiver de l'Amour Bis, ARC Musée d'Art Moderne de la Ville de Paris, 10 février - 13 mars 1994
Frans & Engels
boek